Case report: Challenges in immune reconstitution following hematopoietic stem cell transplantation for CTLA-4 insufficiency-like primary immune regulatory disorders - Margarit-Soler, Adriana; Deyà-Martínez, Àngela; Canizales, Juan Torres; Vlagea, Alexandru; García-García, Ana; Marsal, Júlia; Del Castillo, Maria Trabazo; Planas, Sílvia; Simó, Sílvia; Esteve-Sole, Ana; Grande, María Suárez-Lledó; Badell, Isabel; et al. (Frontiers in Immunology, 2022)
Cytotoxic T-lymphocyte antigen-4 (CTLA-4) haploinsufficiency is a T-cell hyperactivation disorder that can manifest with both immunodeficiency and immune dysregulation. Approximately one-third of patients may present mild symptoms and remain stable under supportive care. The remaining patients may develop severe multiorgan autoimmunity requiring lifelong immunosuppressive treatment. Hematopoietic stem cell transplantation (HSCT) is potentially curable for patients with treatment-resistant immune dysregulation. Nevertheless, little experience is reported regarding the management of complications post-HSCT. We present case 1 (CTLA-4 haploinsufficiency) and case 2 (CTLA-4 insufficiency-like phenotype) manifesting with severe autoimmunity including cytopenia and involvement of the central nervous system (CNS), lung, and gut and variable impairment of humoral responses. Both patients underwent HSCT for which the main complications were persistent mixed chimerism, infections, and immune-mediated complications [graft-versus-host disease (GVHD) and nodular lung disease]. Detailed management and outcomes of therapeutic interventions post-HSCT are discussed. Concretely, post-HSCT abatacept and human leukocyte antigen (HLA)-matched sibling donor lymphocyte infusions may be used to increase T-cell donor chimerism with the aim of correcting the immune phenotype of CTLA-4 haploinsufficiency.